Calcules

posted by .

find y" by implicit differentiation.
4x^3 + 3y^3 = 4
=====================================
4x^3 + 3y^3 = 4
12x + 9yy' = 0
24x + 9(2yy')y' + 9y^2(y") = 0

y" = -6[4x-3y(y')^2] answer. (it this right? )

  • Calcules -

    Your 1st deriv should have been
    12x^2 + 9y^2 y' = 0 ----> y' = -12x^2/(9y^2)

    2nd derivative:
    24x + 9y^2 (y'') + y' (18y) = 0
    replacing y'
    24x + 9y^2 y'' + (-12x^2)/(9y^2) (18y) = 0
    24x + 9y^2 y'' - 24x/y = 0
    times y
    24xy + 9y^3 - 24x = 0
    y'' = (24x - 24xy)/(9y^3) = (8x-8xy)/(3y^3)

    I don't think they wanted to see that y' in your answer.

    btw, how did you ever get you first derivative ?

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Math - Calculus Question.

    hey can someone explain to me the relationship between the chain rule and implicit differentiation?
  2. Calculus 1 - implicit differentiation

    I do not understand implicit differentiation. One of the problems are: find y' by implicit differentiation xy+2x+3x^2=4. I would appreciate any help that can be offered.
  3. Calculus 1 - implicit differentiation

    I do not understand implicit differentiation. One of the problems are: find y' by implicit differentiation xy+2x+3x^2=4. I would appreciate any help that can be offered.
  4. calculus; implicit differentiation

    Use implicit differentiation to find the slope of the tangent line to the curve at the point (4,1) -1x^2 - 4xy + 3y^3 = -29 I differentiated both sides and solved for dy/dx and got 2x-4y/9y^2-4x. Then I plugged in X and Y and got -4/7 …
  5. algebra

    24x^4-12x^3+48x^2/-4x 24x^4-12x^3+12(-1) 24x^4-12x^3+(-12x) 2x^4-12x^3-12x check this problem for me please
  6. Calculus

    How do you use imlicit differentiation to differentiate e^(xy)?
  7. Implicit differentiation calculus

    PLEASE HELP , I DON'T UNDERSTAND find dy/dx by implicit differentiation a) xy + x^5y^2 + 3x^3 - 4 = 1 b) lny = cos x thank you
  8. Calculus: implicit differentiation

    Find dy/dx by implicit differentiation 1. x^3 -xy+ y^2= 7 The given answer is (y-3x^2)/ (2y-x), but I'm not getting it. 2. How would I do this one?
  9. Mathematics

    How do you find the coordinates of the stationary points to this implicit differentiation equation?
  10. Calculus

    use implicit differentiation to find dy/dx if 5xy+x^2y=10 Is this correct answer for this question (-5y-2xy)/(12x)

More Similar Questions